Prevalence and clinical significance of totally occluded infarct-related arteries in patients with non-ST-segment elevation acute coronary syndromes. (1st February 2021) - Almendro-Delia, Manuel; Seoane García, Tania; Villar Calle, Pablo; García González, Néstor; Lorenzo López, Beatriz; Cortés, Francisco Javier; García del Río, Manuel; Ruiz García, María del Pilar; Hidalgo Urbano, Rafael J.; García-Rubira, Juan C.
Abstract: Background Seemingly conflicting findings exist regarding the prognostic impact of totally occluded infarct-related arteries (oIRA) in non-ST elevation acute coronary syndromes (NSTE-ACS). Methods Retrospective analysis of prospective multicenter registry data comprising a single-center NSTE-ACS cohort, aimed at assessing the impact of occluded (TIMI flow 0/1) versus patent culprit vessels (pIRA, TIMI flow 2/3) on the composite endpoint of all-cause death and cardiogenic shock events at 30 days. Results Of 568 patients, 183 (32.5%) had oIRA. Male sex, refractory angina, ECG suggestive of multivessel or left main disease, and larger infarct sizes with inferior/posterolateral wall involvement, were identified as highly specific markers of oIRA. Successful culprit-lesion revascularization occurred more frequently in patent than in oIRA (90% vs. 96%; P = 0.013). Conversely, patients with oIRA more frequently achieved successful revascularization of concurrent non-IRAs including chronic total occlusions than did those with pIRA (28% vs. 3%; P = 0.0005). Multivariate analysis revealed neutral effects of oIRA on outcomes and identified incomplete revascularization as a powerful predictor of mortality. Moderation analysis revealed a significant interaction between completeness of revascularization and IRA patency, whereby among the incompletely revascularized patients, those with oIRA enjoyed a significant survival advantage over their counterparts with pIRA (11.8% vs. 28%, adjusted OR 0.34; 95% CI 0.10–0.73; P interaction = 0.012). Conclusions Approximately one third of NSTE-ACS patients in this cohort had oIRA. However, compared with pIRA, the occurrence of oIRA did not portend poor outcomes, likely resulting from the higher rate of incomplete revascularization and increased risk of subsequent mortality in patients with pIRA. These exploratory findings warrant further investigation. Graphical abstract: Unlabelled Image Highlights: In NSTE-ACS, association between totally occluded culprits and mortality was found neutral Incomplete revascularization, particularly of CTO was associated with increased risk of death Significant interaction emerged between the extent of revascularization and the culprit patency on mortality CTO-PCI largely drived mortality risk regardless of the IRA patency in NSTE-ACS